KEPRIBADIAN PENDIDIK DAN PESERTA DIDIK (KAJIAN HADITS TARBAWI) - Lukito, Lukito (Musawa: Journal for Gender Studies, 2020)
Delivering knowledge is one of a teacher's qualities. It can be performed through teaching, learning, writing books, etc. Knowledge must be absorbed by people in a wider range to give a meaningful impact and to get the society affected by the benefits of it. Aside from implementing the knowledge, a person with knowledge (alim) is required to deliver it to people. The duties of an educator are to convey knowledge, verse, and hadith, instead of keeping it for himself. Keeping for oneself means not answering others’ difficulties or not sharing the book he reads. Teachers' love for students is shown by teaching them ethics and necessary things in life and the afterlife. Islam cares about children and women and never differentiates them from the men. Islam motivates people who are tested with having daughters, but to be grateful and taking their education into account; their daughters will later be a barrier for them from entering into hell.